EFFECTIVENESS OF INSTRUCTIONAL MEDIA BASED GAME ON MATHEMATICS AT VOCATIONAL HIGH SCHOOL - Rizky EmaWulansari, Deno Puyada, IndraWijaya & KasmanRukun (International Journal of Research Science and Management, 2017)
Instructional Media was a tool or form of stimulus which serves to submitted a learning massage. Computer could be used as instructional media. Instructional media of computer could facilitate student to independent learning. Based on observation, researcher found that using of instructional media had not been maximal, just using whiteboard and power point only. This research aimed at developed instructional media based game on mathematics at Vocational High School. Model of this research was 4D (four-D) model that was developed by S. Thiagarajan et al. There were four steps in 4D (four-D) model, were follow: define (define phase), design (design phase), develop (development phase), disseminate (disseminate phase). Electivity test include in develop phase. Electivity test was done with using pretest and posttest that given to students. The effectiveness of instructional media based game was expressed effective for improving results of student learning because 82,1% of students have reached KKM